A study on vitamin D levels in preterm and term neonates and their mothers - Thomas, Deepa J.; Khan, Habeeb U.; Paul, Saritha; D., Jaidev M.; Hegde, Pavan (International Journal of Contemporary Pediatrics, 2020)
Background: Vitamin D is a fat-soluble vitamin which has immunomodulatory and anti-inflammatory effects. Vitamin D deficiency is a worldwide problem and yet is one of the most under diagnosed and under treated nutritional deficiency. Despite India being in the tropical zone with plentiful sunlight, there is a wide prevalence of vitamin D deficiency. Methods: Cross sectional descriptive study done in a tertiary care hospital involving 30 mother baby dyads equally divided into term and preterm babies. Maternal vitamin D levels (before delivery) and cord blood vitamin D levels (after delivery) were estimated. Results: All the mothers had low vitamin D levels, 93% having deficiency and 7% having insufficiency. The maternal vitamin D levels correlated with cord blood vitamin D levels. There was significant correlation between maternal vitamin D levels and cord blood vitamin D levels with maternal age and parity. There was no correlation between maternal vitamin D levels with gestational age, sociodemographic profile or neonatal anthropometry. Conclusions: Vitamin D deficiency is widely prevalent even in well-nourished mothers. Vitamin D supplementation may be helpful in antenatal mothers. Larger studies are needed to study the prevalence of vitamin D deficiency in mothers and babies and look for effectiveness of supplementation.